Poland Syndrome with Unusual Associated Anomalies: A Case Report - Naher, Begum Sharifun; Shahidullah, Md; Mannan, MA; Noor, Khaled; Dey, Arjun Chandra (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v30i1.6181 Bangladesh J Child Health 2006; VOL 30 (1/2/3): 29-31